Instilling the Value of Tolerance in Overcoming Bullying Behavior in Class IV Students at SDN 1 Gumantar - Sugianto, Sugianto; Hadiyaturrido, Hadiyaturrido; Musafir, Musafir (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This research was conducted with the aim of finding out the instillation of tolerance values in overcoming bullying behavior in class IV students at SD Negeri 1 Gumantar. The type of research used is qualitative. The subjects of this research are school principals, class teachers and students. The data collection process includes observation, interviews, and documentation. The data analysis techniques used in this research consist of data collection, data reduction, data presentation, and drawing conclusions. The results of the research show that the teacher's efforts to instill the value of tolerance as an effort to overcome bullying behavior among students at SD Negeri 1 Gumantar are carried out using a habituation pattern, namely, in instilling the value of tolerance, children are always accustomed to saying help when they need help from the teacher and Get used to saying sorry when you make a mistake. Seating arrangements, namely, can help students interact more closely regardless of background. teaches mutual respect, that is, develops children emotionally to respect others. encouraging discussion, namely, through group discussions students can work together without paying attention to background aspects.